2021
DOI: 10.1177/08980101211021219
|View full text |Cite|
|
Sign up to set email alerts
|

Despite Symptom Severity, do Nursing Home Residents Experience Joy-of-Life? The Associations Between Joy-of-Life and Symptom Severity in Norwegian Nursing Home Residents

Abstract: Background: Finding new approaches to increase health and well-being among nursing home (NH) residents is highly warranted. From a holistic perspective, several Norwegian municipalities have implemented the certification scheme framed “Joy-of-Life Nursing Home” Aims: In a holistic perspective on NH care, this study investigated if NH residents despite potential symptom severity experience joy-of-life (JoL). Therefore, we examined the frequency of common symptoms and the association between common symptoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…Moving to a NH result from numerous losses, illnesses, disabilities, loss of functions and social relations and facing an end‐of‐life situation. Accordingly, the long‐term NH population is characterised by a high incidence of chronic illness and functional impairments (Hoben et al, 2016), multiple simultaneous and complex diagnoses with a severe symptom burden, impaired functioning, various losses and fewer social relationships (Haugan, 2014b; Rinnan et al, 2022; Söderbacka et al, 2017). All of these increase an individual's vulnerability and distress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moving to a NH result from numerous losses, illnesses, disabilities, loss of functions and social relations and facing an end‐of‐life situation. Accordingly, the long‐term NH population is characterised by a high incidence of chronic illness and functional impairments (Hoben et al, 2016), multiple simultaneous and complex diagnoses with a severe symptom burden, impaired functioning, various losses and fewer social relationships (Haugan, 2014b; Rinnan et al, 2022; Söderbacka et al, 2017). All of these increase an individual's vulnerability and distress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, symptom severity seems constantly high; in 2009 (Haugan, 2014d) and 2018 (Rinnan et al, 2022) symptom severity was reported respectively as: 57% and 54% fatigue, 43% and 52% constipation, 49% and 45% pain, 41% and 43% dyspnoea, 38% and 32% insomnia, 25% and 22% appetite loss, 18% and 20% nausea, 12% and 20% anxiety and 30% and 23% reported depressive symptoms. Nevertheless, a recent study demonstrates that despite these ailments, about 50% of residents in Norwegian NHs report a high joy‐of‐life (Rinnan et al, 2022). Globally, anxiety and depression are commonly reported among NH residents (Beutel et al, 2017; Drageset & Haugan, 2021; Hawkley & Cacioppo, 2010); compared to older people living in their own homes NH residents report higher levels of depression and anxiety (Šare et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…V literaturi sta osamljenost in depresija opredeljeni kot faktorja tveganja, ki lahko ogrozita čustveno počutje starejših (Routsaldo et al, 2006;Savikko, 2008). Populacija DSO se sooča z visoko starostjo, šibkostjo, pridruženimi boleznimi, umrljivostjo, invalidnostjo, nemočjo, odvisnostjo, ranljivostjo, slabšim splošnim zdravjem in visokim simptomatskim bremenom (Haugan, 2014a;Rinnan et al, 2022), kar vodi v bivanje na zgolj preživetveni ravni (Hoben et al, 2016). Eksistencialno trpljenje stanovalcev DSO se odraža tudi v prisotnosti eksistencialnih vprašanj, kot so dokončnost življenja, socialna izolacija, osamljenost in pomanjkanje smisla (Sanderson & Scherbov, 2010;Drageset & Haugan, 2021).…”
Section: Slovenian Translation/prevod V Slovenščinounclassified
“…Loneliness and depression have been identified as risks to the emotional well-being of older people (Routsaldo et al, 2006;Savikko, 2008). the NH population is characterised by advanced age, frailty, concurrent diagnoses, mortality, disability, powerlessness, dependency, vulnerability, poor general health and high symptom burden (Haugan, 2014a;Rinnan et al, 2022), which implies a highly existential state of living (Hoben et al, 2016). Consequently, existential issues such as the finality of life, social isolation, loneliness and meaninglessness are indicative of existential suffering among NH residents (Sanderson & Scherbov, 2010;Drageset & Haugan, 2021).…”
mentioning
confidence: 99%